‘Scholarship and Empire’: Matthew Rampley, The Vienna School of Art History: Empire and the Politics of Scholarship, 1847-1918, University Park: Penn State Press, 2013 - Margaret Olin (Journal of Art Historiography, 2014)
Matthew Rampley’s The Vienna School of Art History examines the early era of the famed group of art historians, curators and art functionaries against the Habsburg Empire that framed their enterprise. It takes into account the centrifugal forces of identity, nationalism and Imperial ideologies that informed their ideas and preferences. A desideratum is the project of relating formal analyses by the thinkers he studies to the ideological allegiances that he uncovers in their thought.